1995
DOI: 10.1017/s0022215100131330
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent sialadenoma papilliferum of the buccal mucosa

Abstract: Sialadenoma papilliferum is a rare, benign, exophytic tumour of the salivary glands. The prognosis is exceptionally good. Since the lesion was first described, 30 cases have been reported in the English literature. and only one of these is known to have recurred.A case of sialadenoma papilliferum occurring in the buccal mucosa with recurrence three years after local excision, is presented. The literature is briefly discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Sialadenoma papilliferum has been considered to be a benign tumor with limited potential for local aggressiveness. Based on 20 reported cases with adequate follow up, two lesions recurred at 3 years: one from the buccal mucosa 22 and one from the junction of the hard and soft palate 23 . An extremely rare case, however, of sialadenoma papilliferum of the palate with epithelial–myoepithelial carcinoma and high‐grade carcinoma has recently been reported 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Sialadenoma papilliferum has been considered to be a benign tumor with limited potential for local aggressiveness. Based on 20 reported cases with adequate follow up, two lesions recurred at 3 years: one from the buccal mucosa 22 and one from the junction of the hard and soft palate 23 . An extremely rare case, however, of sialadenoma papilliferum of the palate with epithelial–myoepithelial carcinoma and high‐grade carcinoma has recently been reported 24 .…”
Section: Discussionmentioning
confidence: 99%
“…It is both an exophytic and endophytic papillary lesion histologically resembling syringocystadenoma papilliferum of sweat gland. The tumor is considered benign although rare recurrent cases have been reported [2, 3]. Three cases of malignant transformation of sialadenoma papilliferum have been described in the literature [46].…”
Section: Introductionmentioning
confidence: 99%
“…The surface of the tumor is covered by acanthotic stratified squamous epithelium, which merges into the papillary fronds formed by the ductal proliferation in the deep areas. According to the approximately 50 reported cases, SP is considered to be a benign tumor with an exceptionally good prognosis, although post-operative recurrence was observed in two cases [23,24]. Solomon et al [27] reported an intra-oral malignant neoplasm as a possible malignant SP, but subsequent studies have discounted their interpretation [3,9].…”
Section: Introductionmentioning
confidence: 99%